Pengaruh Keamanan, Kemudahan, Kepercayaan dan Pengalaman Berbelanja terhadap Minat Beli Online pada Situs Jual Beli Shopee - Ratna Furi; Nur Hidayati; Siti Asiyah (UNIVERSITAS ISLAM MALANG, 2020)
AbstractInternet technology development has brought real impacts which enable people to do daily life in more convenient way, for instance, a convenience of doing shopping. Many people are more attracted to do shopping due to safety guarantee, convenient transaction, reliability on shopping site and contented shopping experiences which are offered by shopping site. This research aims at identifying effect of safety, convenience, reliability and shopping experience on interest of shop at shopping site called Shopee. Population in is this research is the students of Universitas Islam Malang who make purchase on shopping site Shopee in which samples are taken from 96 respondents who are selected by applying purposive sampling technique. Hypothesis in this research is investigated by applying double linear regression analysis. Result of this research suggested that safety, convenience, reliability and shopping experience has simultaneously affected shopping interest. Variable of safety, convenience, reliability and shopping experience has positive and significant effect of shopping interest. Keyword: Safety, Convenience, Reliability, Shopping Experience and Shopping Interest